2022
DOI: 10.1007/s00590-022-03240-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of cerclage wiring in the management of subtrochanteric and reverse oblique intertrochanteric fractures: a meta-analysis of comparative studies

Abstract: Purpose Subtrochanteric and reverse oblique intertrochanteric fractures are challenging and often difficult to reduce. While intramedullary nailing (IMN) is considered the standard treatment, achieving anatomic reduction prior to fixation is essential. This study aimed to assess the impact of cerclage wiring with IMN on the outcomes and complication rate in treating subtrochanteric and reverse oblique intertrochanteric fractures. Methods This meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The data on this are very controversial. While some studies assume a delay in healing [22,23], others have even found an acceleration in healing times [24] or no significant difference [25]. A major advantage of using cerclage is improvement in the anatomical position of the fracture fragments in relation to each other and the resulting greater stability [23,25], which can have an effect not only on blood flow but also on the success of fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…The data on this are very controversial. While some studies assume a delay in healing [22,23], others have even found an acceleration in healing times [24] or no significant difference [25]. A major advantage of using cerclage is improvement in the anatomical position of the fracture fragments in relation to each other and the resulting greater stability [23,25], which can have an effect not only on blood flow but also on the success of fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…13 Application of a circumferential cerclage cable after intramedullary fixation of reverse oblique intertrochanteric fractures reduces the risk of implant failure. 14,15 The quantity and range of the posteromedial fragment significantly correlates with postoperative telescoping and varus collapse of the femoral head and neck component. 2 Anteromedial cortical support reduction for unstable intertrochanteric fractures introduced by Chang and colleagues in 2015 is an extension of the nonanatomic positive cortex buttress concept by Gotfried et al 12,16 This reduction aims at using the medial wall of the femur shaft fragment as a functional buttress for the medial cortex of the neck fragment.…”
Section: Reductionmentioning
confidence: 99%